Analisis Marketing Digital Merek Skincare Npure di Instagram - Fatiha Aizza Adzra; Maya Amalia Oesman Palapah (Bandung Conference Series: Public Relations, 2024)
Abstract. Skincare NPure has many fans in Indonesia. One way for NPure to market its products is through the digital platform Instagram. NPure uses the reels service to sell its products. One of their Instagram upload is titled "Grebek Skincare" which describes the benefits of each NPure product. Unfortunately, this content was not very successful due to public lack of trust in NPure products. The purpose of this research is to find out how NPure did digital marketing, to find out the impact of digital marketing, and to find out how to increase NPure's digital marketing. This research is a qualitative research using case study method. The subject of this study is the members of the NPure community called Pure Mates who hold a position in the form of a content creator or KOL (Leader of Opinion). Based on the results of the digital marketing analysis of the Npure skincare brand, it is found that Npure uses and maximizes Instagram features to promote and educate consumers, includes consumers with activities organized by Npure and collaborates with communities that have the same mission as Npure. Npure also posts its content to TikTok to expand its reach and optimize the use of social media. Npure also conducts research before creating content according to audience preferences and tailors followers' interests in order to create interesting and relevant content. This has proven to be effective in increasing public trust in Npure's products. Abstrak. Skincare NPure memiliki banyak peminat di Indonesia. Salah satu cara NPure untuk memasarkan produknya adalah menggunakan platform digital Instagram. NPure menggunakan fitur reels untuk memasarkan produknya. Salah satu unggahan instagramnya yang berjudul “Grebek Skincare” yang menjelaskan manfaat dari tiap produk NPure. Sayangnya konten tersebut kurang berhasil karena kurangnya kepercayaan masyarakat terhadap produk NPure. Tujuan penelitian ini ialah untuk mengetahui cara yang sudah dilakukan NPure dalam marketing digital, mengetahui dampak digital marketing dan mengetahui cara memaksimalkan digital marketing NPure. Desain penelitian ini adalah penelitian kualitatif menggunakan pendekatan studi kasus. Subjek pada penelitian ini yaitu anggota komunitas NPure yang bernama Pure Mates yang memiliki jabatan berupa content creator atau KOL (Key Opinion Leader). Berdasarkan dari hasil penelitian analisis marketing digital merek skincare Npure ditemukan bahwa, Npure memakai dan memaksimalkan fitur-fitur Instagram untuk mempromosikan dan mengedukasi konsumen, menyertakan konsumen dengan kegiatan yang diselenggarakan oleh Npure serta bekerjasama dengan komunitas yang memiliki misi yang sama dengan Npure. Npure pun memposting kontennya ke TikTok untuk memperluas jangkauan dan mengoptimalkan penggunaan media sosial. Npure juga melakukan riset sebelum membuat konten sesuai dengan preferensi audiens dan menyesuaikan minat followers agar dapat menciptakan konten yang menarik dan relevan. Hal ini terbukti efektif untuk meningkatkan kepercayaan masyarakat terhadap produk Npure.